Developing and validating a 2D digital version of the Brazilian Children's anxiety questionnaire - Martins, Valquiria Moreira Lacerda [UNESP]; da Silva, Juliana Bastoni; Francisco, Janaina Chinaque [UNESP]; Santos, Gabriela Rossi Dos [UNESP]; dos Santos, Gabriely Silva [UNESP]; Nilsson, Stefan; Garcia de Avila, Marla Andreia [UNESP] (Elsevier, 2024)
Purpose: This study aims to transpose the printed Brazilian Children's Anxiety Questionnaire (CAQ BR) into a 2D digital format, validate it with nurses and hospitalized children, and analyze the association between the printed and 2D digital format versions. Design and method: This is a descriptive and multicentric study, conducted from 2021 to 2022 on working in pediatric care at two hospitals in Brazil. The nurses analyzed the printed and digital instruments and subsequently applied them to a child and proposed suggestions. A cutoff score of 0.80 on the content validity index was used; items that scored an average lower than the CVI in the study were adequate. Eighty children responded to the questionnaires sequentially according to the randomization table. A 90% agreement rate was used. Results: The digital instrument was validated in content by 51 experts, with a CVI of 0.95. Face validation data for 80 children (mean age = 7.9 years) shows a 90% agreement rate. The intraclass correlation index for the general score was 0.87 and 95% CI (0.79–0.91), which shows good stability of the children's responses in both questionnaires. In addition, 59% (n = 47) of the children reported a preference for the digital questionnaire. Conclusions: The digital CAQ BR can be used as an audiovisual instrument by nurses when implementing the systematization of nursing care in pediatrics. Practical implications: The digital 2D version was successfully applied and can be used in hospitals to measure children's self-reported anxiety.
Keywords: Anxiety; Children; Digital health; Nursing process; Pediatric nursing